Nanoporous materials for environmental applications - Chun-Yang, Yin, Dr.; Savory, Robert Mikhail, Dr.; Goh, Bee Min; Mohamad El-Harbawi, Dr.; Mohd. Jindra, Arus (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/